Toothpaste tube and composition

CN123036205APending Publication Date: 2026-11-03UNILEVER IP HLDG BV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580026093.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-03
Filing Date
2025-03-10
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing toothpaste compositions suffer from fragrance impact and stability issues during packaging, making it difficult to maintain good barrier properties and storage stability in recyclable laminated tubes.

Method used

Plastic-based laminated tubes employing a specific multi-layered laminated structure, including a barrier layer consisting of an ethyl vinyl alcohol interlayer and a high-density polyethylene intermediate layer, combined with extrusion lamination technology to form a multi-layered structure, ensure reduced fragrance migration and absorption while maintaining cleaning power and physical stability.

Benefits of technology

Maintaining the flavor properties and consumer-related properties of the toothpaste composition over an extended shelf life, providing good chemical and physical stability, and enabling the recyclability of the laminated tube.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to packaged products, in particular, the present invention relates to packaged toothpaste compositions packaged in recyclable plastic-based laminate tubes. The present inventors have found that a packaged product having a toothpaste composition comprising a perfume and enclosed in a plastic-based laminate tube having a specific multi-layer laminate structure provides good chemical and physical stability to the toothpaste composition and desirable consumer-related properties (e.g. desirable viscosity and yield stress) as well as good perfume performance. It was further found that a toothpaste composition having a perfume and packaged in a plastic-based laminate tube maintains acceptable cleaning ability and physical stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to packaged products, and more specifically, to packaged toothpaste compositions packaged in recyclable plastic-based laminated tubes. Background Technology

[0002] Toothpaste compositions are typically packaged in collapsible tubes. These tubes are usually made of laminate, i.e., multiple layers of material, with the layers bonded together, for example, by co-extrusion or adhesive lamination.

[0003] Plastic laminated tubes typically comprise an inner polyolefin resin layer in direct contact with the composition, and at least one intermediate barrier layer comprising an aluminum foil layer that inhibits the loss of fragrance from the composition. The outer layer is typically made of polyolefin resin, and one of these outer layers may be colored white and have a printed logo, which has a transparent polyolefin laminate overlay to protect the logo. Aluminum-based laminations are commonly referred to as aluminum-based laminations (ABLs). Aluminum-based tubes provide good water and gas barrier properties and are preferred for packaging toothpaste compositions. Typically, a thin layer of aluminum foil of about 5 µm to 12 µm is sufficient. Typically, the ABL lamination is made of polyolefin, particularly polyethylene, such as high-density polyethylene (HDPE). Tubes made of aluminum-based laminations are called ABL tubes.

[0004] In recent years, in order to address the recyclability issues associated with aluminum-based laminations, plastic-based laminations (PBLs) using EVOH as a barrier layer have been developed.

[0005] EP2155488 B1 discloses a collapsible tube container formed from one or more blown film polymer materials, particularly a collapsible tube container including a side joint weld.

[0006] US2023 / 405982 A1 discloses laminated tubes containing post-industrial and / or post-consumer recycled resins.

[0007] There is a need to provide packaged toothpaste compositions which are packaged in recyclable and sustainable laminated tubes, wherein the laminated tubes provide sufficient barrier properties.

[0008] Toothpaste compositions are formulated using several ingredients, such as abrasives, fragrance components, specific pH ranges, antimicrobial agents, sorbitol, various gums, and amino acids, to provide the desired cleaning performance and benefits such as anti-caries activity. The fragrance impact and profile of the composition, as well as its stability, are strongly influenced by the laminated tube that packages it, and the packaging needs to be designed to ensure that the fragrance profile and impact are not excessively affected during storage. It is desirable that the composition retain its desired properties and remain stable during storage while modifying the structure and composition of the laminated tube to provide improved recyclability and sustainability. Summary of the Invention

[0009] The inventors have discovered that packaged products having a fragrance-containing toothpaste composition, when packaged in a plastic-based laminated tube having a specific multilayer laminated structure according to the invention, provide good fragrance impact and fragrance strength over an extended shelf life.

[0010] Surprisingly, the toothpaste composition was found to have good chemical and physical stability as well as desired consumer-related properties (such as desired viscosity and yield stress).

[0011] The inventors have further discovered that packaged products having a fragrance-containing toothpaste composition, when packaged in a laminated tube having a specific multilayer lamination structure according to the invention, provide improved fragrance performance over an extended shelf life. It has also been discovered that the fragrance-containing toothpaste composition exhibits reduced migration and absorption of the fragrance into the laminated tube having a specific multilayer lamination structure according to the invention.

[0012] Further findings revealed that toothpaste compositions containing fragrance and packaged in plastic-based laminated tubes maintained acceptable cleaning power and physical stability.

[0013] According to a first aspect of the invention, a packaged product is provided, comprising: i. A flexible laminated tube, said flexible laminated tube comprising a multilayer laminated structure; and, ii. A toothpaste composition encapsulated in a flexible tube; The toothpaste composition said therein contains fragrance; and, The multilayer laminated structure includes a barrier layer. The barrier layer is a multilayer structure having a barrier material sublayer, the barrier material sublayer comprising ethyl vinyl alcohol sandwiched between a first intermediate sublayer and a second intermediate sublayer, wherein the first intermediate sublayer and / or the second intermediate sublayer comprises high-density polyethylene (HDPE). The multilayer laminated structure comprises 45% to 90% by weight of at least one polyethylene, wherein the at least one polyethylene has a content of 0.91 g / cm³. 3 Up to 0.99 g / cm 3 The density of the range; and the multilayer laminated structure comprising at least one extruded laminate layer. Detailed Implementation

[0014] According to a first aspect, the present invention provides a toothpaste composition and a laminated tube.

[0015] As described herein, a “multilayer structure” refers to a structure having more than one layer. For example, the multilayer structure (e.g., a membrane) may have two, three, four, five, or more layers. The multilayer laminated structure forms a wall between the packaged toothpaste composition and the surrounding environment, and the multilayer laminated structure includes at least two membranes.

[0016] As used herein, the term "lamination" refers to the process of joining two or more membranes together by extruding layers in the shape of membranes. Thus, the extruded layers act as a binder. One or more of these membranes, joined together to form a multilayer laminated structure, are preferably prepared by a blown film process. The membranes prepared by the blown film process can preferably be multilayer membranes.

[0017] As described herein, "polyethylene" or "ethylene-based polymer" means polymers comprising more than 50 mol% of units derived from ethylene monomers. This includes ethylene-based homopolymers, ethylene copolymers (meaning units derived from ethylene and additional monomers), and ethylene interpolymers (meaning units derived from ethylene and at least one additional comonomer). These comonomers may include C3-C 12 α-Olefin comonomers. Forms of polyethylene include, but are not limited to, low-density polyethylene (LDPE); linear low-density polyethylene (LLDPE); ultra-low-density polyethylene (ULDPE); very low-density polyethylene (VLDPE); single-site catalytic linear low-density polyethylene… including both linear low-density resin and essentially linear low-density resin (m-LLDPE); medium-density polyethylene (MDPE); and high-density polyethylene (HDPE).

[0018] The term "LDPE," as described herein, can also be referred to as "high-pressure ethylene polymer" or "highly branched polyethylene," and is defined as meaning that the polymer is partially or wholly homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator (e.g., peroxide). LDPE resin typically has a density of 0.916 g / cm³. 3Up to 0.940 g / cm 3 The density of the range.

[0019] Preferably, LDPE means having a content of less than or equal to 0.930 g / cm³. 3 The density is low-density polyethylene. More preferably, when measured using the ASTM D792 method, the LDPE has a density of 0.91 g / cm³. 3 Up to 0.930 g / cm 3 The density ranges from [specific value missing]. Preferably, the LDPE has a melt flow index of 0.75 g / 10 min at 190°C and 2.16 kg when measured using the ASTM 1238 test method. Suitable commercially available examples of LDPE include ExxonMobil LDPE LD 150BW from ExxonMobil.

[0020] As described herein, the term "LLDPE" can include resins prepared using Ziegler-Natta catalyst systems and resins prepared using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphine imides, and restricted geometry catalysts; and resins prepared using post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also known as polyvalent aryloxy ether catalysts). LLDPEs include linear, substantially linear, or heterogeneous ethylene-based copolymers or homopolymers. LLDPEs contain fewer long-chain branchings compared to LDPEs and comprise substantially linear ethylene polymers. The LLDPE resins can be prepared via gas-phase, solution-phase, or slurry polymerization or any combination thereof; using any type of reactor or reactor configuration known in the art. The LLDPE resins can be prepared via gas-phase, solution-phase, or slurry polymerization or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0021] Preferably, LLDPE means having a content of less than 0.930 g / cm³. 3 The multilayer laminated structure comprises linear low-density polyethylene (LLDPE). Suitable LLDPEs include copolymers of ethylene and α-olefins. α-olefins include 1-butene, 1-hexene, 1-octene, and mixtures thereof. Suitable commercially available examples of LLDPE include Elite from The Dow Chemical Company. TM 5400.

[0022] The term "MDPE" refers to a material with a density of 0.926 g / cm³. 3 Up to 0.941 g / cm 3MDPE is polyethylene with a specific density. MDPE is typically prepared using chromium or Ziegler-Natta catalysts or single-site catalysts (including, but not limited to, bis-ceramic catalysts and restricted geometry catalysts).

[0023] The term "HDPE" refers to a material with a density of 0.940 g / cm³. 3 Or higher density polyethylene, which is typically prepared using Ziegler-Natta catalysts, chromium catalysts or even metallocene catalysts.

[0024] Preferably, HDPE refers to a material with a density greater than 0.935 g / cm³. 3 The density of the high-density polyethylene is [not specified]. More preferably, when measured using the ASTM D792 method, the HDPE has a density of 0.941 g / cm³. 3 Up to 0.969 g / cm 3 The density ranges from [specific value missing]. Preferably, when measured using the ASTM 1238 test method, the HDPE has a melt flow index of less than 4 g / 10 min at 190°C and 2.16 kg, and still preferably has a melt flow index of 0.3 to 2.5 g / 10 min. Suitable commercially available examples of HDPE include Elite from The Dow Chemical Company. TM AT 6900.

[0025] As used herein, “melt index” (I2) is a measure of the melt flow rate of a polymer, measured by ASTM D1238 at a temperature of 190°C and a load of 2.16 kg. “Melt index” may also be referred to herein as “I2” or “melt flow rate”.

[0026] As used in this article, the term "membrane" refers to a single-layer or multi-layer structure prepared using a blown film process.

[0027] As used herein, the term "laminate" refers to a multilayer structure comprising at least two film layers and at least one extrusion lamination layer. The lamination surrounds the packaged toothpaste composition and forms a wall between the packaged product and the surrounding environment.

[0028] Flexible laminate According to a first aspect, the present invention provides a flexible laminated tube. The laminated tube preferably refers to the body of the tube, which includes a shoulder.

[0029] Preferably, the laminated tube comprises 25% to 90% by weight, still preferably 45% to 90% by weight, more preferably 50% to 90% by weight, still preferably 60% to 90% by weight, and even more preferably 80% to 90% by weight of at least one type of polyethylene, said at least one type of polyethylene having a content of 0.94 g / cm³. 3 Up to 0.97 g / cm 3 The density ranges from [specific value range]. Preferably, the laminated tube contains 45% to 90% by weight, more preferably 50% to 90% by weight, still preferably 60% to 90% by weight, and even more preferably 80% to 90% by weight of at least one polyethylene or ethylene-based polymer, said at least one polyethylene or ethylene-based polymer having a density of 0.94 g / cm³. 3 Up to 0.97 g / cm 3 The density ranges from [specific value]. Preferably, the at least one polyethylene is HDPE, MDPE, or a combination thereof.

[0030] The flexible laminated tube includes a multilayer laminated structure comprising 45% to 100% by weight, more preferably 45% to 98% by weight, still preferably 45% to 95% by weight, still more preferably 45% to 90% by weight of polyethylene or an ethylene-based polymer, and wherein the multilayer laminated structure has a barrier layer.

[0031] Preferably, the flexible laminated tube includes a tube body portion comprising a multi-layered laminated structure and a tube shoulder comprising a neck portion.

[0032] The shoulder can preferably be formed together with the tube body. Preferably, the shoulder can also be prepared separately and attached to the tube body portion. Alternatively, the foldable tube according to the invention preferably does not have a shoulder. Preferably, the shoulder portion can contain 55% to 100% by weight of polyethylene or an ethylene-based polymer. Preferably, the shoulder portion can contain an ethylene-vinyl alcohol copolymer, preferably, when present, the amount of the ethylene-vinyl alcohol copolymer does not exceed 5% by weight. More preferably, the shoulder portion can contain more than 60% by weight, still more preferably 50% to 100% by weight of polyethylene or an ethylene-based polymer. Preferably, the polyethylene is HDPE. More preferably, the shoulder portion is 100% polyethylene or an ethylene-based polymer. Preferably, the HDPE has a content of 0.94 g / cm³. 3 Up to 0.96 g / cm 3The density ranges from 1 to 3 and the melt flow index ranges from 1 to 3. Preferably, the tube shoulder may include an internal barrier liner installed inside the tube shoulder. Preferably, the tube shoulder can be molded by general molding methods, including extrusion molding, compression molding, and injection molding. Further, the prepared tube shoulder is bonded to a separately prepared tube body or bonded to a tube body formed in-line to complete a foldable laminated tube.

[0033] The laminated tube includes a neck portion, preferably a shoulder portion that includes the neck portion, and the neck portion is formed together with the shoulder portion. The neck portion has an externally threaded portion for releasable engagement with the tube cap. The neck portion has an orifice communicating with an internal cavity of the tube body. Preferably, the neck portion may contain 55% to 100% polyethylene or an ethylene-based polymer, and still preferably, the neck portion contains 100% polyethylene or an ethylene-based polymer. Preferably, the neck portion may contain an ethylene-vinyl alcohol copolymer, and when present, the amount of the ethylene-vinyl alcohol copolymer does not exceed 5% by weight. More preferably, the neck portion is 100% polyethylene or an ethylene-based polymer. Preferably, the tube shoulder may include an internal barrier liner installed within the tube shoulder.

[0034] Preferably, the laminated tube includes a cylindrical body for storing packaged products, a shoulder with a neck portion, and means for capping or closing the tube, the neck portion including an outlet for dispensing the packaged products, wherein the body is preferably made of a multilayer laminated structure of the first aspect of the invention. The body may be externally provided with printing, which is mostly pre-applied. Preferably, the shoulder portion has greater rigidity compared to the tube body portion.

[0035] Preferably, the ellipticity of the tube body portion is in the range of 0 to 6%. The cap may also be optional, as it is a separate product manufactured using standard industrial methods. Several methods for manufacturing laminated tubes are well known in the art.

[0036] When the intended application is the manufacture of foldable laminated tubes, the membrane, comprising the outer and inner layers of the laminated structure, should be able to be overlapped and sealed (also known as a side seam), preferably by applying heat so that the sides can be sealed after the product is filled. In such cases, the membrane present in the innermost layer of the multilayer laminated structure should also be self-bonded so that the bottom of the tube can be sealed after the product is filled.

[0037] In the conventional method of manufacturing the tube, the body and the shoulder are manufactured separately or may be manufactured inline and then welded together. The cap of the tube is typically manufactured separately.

[0038] In manufacturing the tube, the multilayer lamination is introduced into an apparatus that provides a preform with a body shape and an expansion hub for expanding the membrane to the required size. Guiding ensures that the edges of the multilayer lamination overlap. The edges are welded together using a fully continuous thermal welding system. The lamination is cut to a specific size using a rotary cutter, thus obtaining a tube of the required length. The resulting tube is placed on a compression mandrel.

[0039] The upper or shoulder portion of the tube is pressed into the correct shape and required size in a separate press, providing a small amount of molten multilayer packaging film. The compression mandrel providing the tube body is introduced into the press, where the shoulder portion is pressed and welded to it. The press is cooled, the tube is removed from the press, and transferred to another device, where each tube is provided with a cap. The apparatus for manufacturing such tubes is available from various suppliers such as AISA and PSG. The tube is fed to a filling device and filled with the desired cosmetic product through a subsequently heat-sealed bottom.

[0040] Multilayer laminated structure According to a first aspect, the present invention provides a laminated tube comprising a multi-layered laminated structure. The laminated tube is preferably a foldable flexible tube.

[0041] The multilayer laminate structure comprises 45% to 90% by weight of at least one type of polyethylene. The multilayer laminate structure comprises at least one type of polyethylene with a content of 0.91 g / cm³. 3 Up to 0.99 g / cm 3 The polyethylene has a density within the range specified. Preferably, the multilayer laminated structure according to the invention has a density of 0.94 g / cm³. 3 Up to 0.99 g / cm 3 The overall density range. Preferably, the at least one polyethylene is selected from high-density polyethylene (HDPE), medium-density polyethylene (MDPE), and combinations thereof.

[0042] Preferably, the multilayer laminate structure includes at least an HDPE layer surrounding the barrier layer. More preferably, the multilayer laminate structure includes an HDPE layer on either side of the barrier layer.

[0043] In a further preferred embodiment, the multilayer laminate contains, by weight of the total multilayer laminate, no more than 70% by weight, more preferably no more than 49% by weight, and even more preferably no more than 37% by weight of at least one polyethylene having a content of 0.94 g / cm³. 3 Up to 0.97 g / cm 3 The density of the range.

[0044] In a preferred aspect, the total HDPE content in the multilayer laminate structure does not exceed 70% by weight, more preferably not more than 49% by weight, and even more preferably not more than 37% by weight, based on the total weight of the multilayer laminate structure.

[0045] Preferably, the total HDPE content in the multilayer laminated structure is 10% to 70% by weight, more preferably 15% to 60% by weight, still preferably 20% to 49% by weight, and even more preferably 20% to 37% by weight, based on the total weight of the multilayer laminated structure.

[0046] More preferably, the multilayer laminated structure includes: i) A printable layer comprising HDPE and preferably at least one of LDPE or LLDPE; ii) A sealing layer comprising polyethylene, wherein the polyethylene comprises HDPE; iii) The barrier layer between them; and, iv) A first extruded layer for laminating the barrier layer to the printable layer, and preferably a second extruded layer for laminating the barrier layer to the sealing layer.

[0047] Preferably, the printable layer does not contain MDPE. Preferably, the printable layer contains HDPE.

[0048] Preferably, the printable layer comprises HDPE and at least one of LDPE or LLDPE. More preferably, the printable layer does not contain MDPE and comprises HDPE. Even more preferably, the printable layer does not contain MDPE and comprises HDPE and at least one of LDPE or LLDPE.

[0049] The multilayer laminate structure includes a first extruded layer between the printable layer and the barrier layer, wherein the extruded layer is formed by extruding a polymer into a film for extrusion lamination of the printable layer and the barrier layer.

[0050] The multilayer laminated structure includes a second extruded layer between the sealing layer and the barrier layer, wherein the extruded layer is formed by extruding a polymer into a film for extrusion lamination of the sealing layer and the barrier layer.

[0051] Printable layer Preferably, the multilayer laminate structure includes a printable layer.

[0052] As used herein, the term "printable layer" refers to a single-layer or multi-layer film. Preferably, the film is a blown film. As used herein, the top printable layer refers to the layer furthest from the product (e.g., toothpaste) when the product is packaged in a package (e.g., a tube) made of the multi-layer laminated structure. This layer is preferably printed.

[0053] Preferably, the top printable film is laminated to the barrier film by an extruded layer extruded in the shape of a film. Thus, the extruded layer acts as an adhesive to form the top printable layer and the barrier layer of the multilayer laminated structure. The extruded layer preferably comprises LDPE.

[0054] Preferably, the printable layer comprises HDPE. More preferably, the printable layer comprises HDPE and at least one of LDPE or LLDPE.

[0055] The top printable layer preferably does not contain MDPE, meaning that the printable layer contains less than 3% by weight of MDPE, still preferably less than 1% by weight of MDPE, and most preferably 0% by weight of MDPE. Preferably, the printable layer contains at least one of HDPE and LDPE or LLDPE, wherein the amount of HDPE in the printable layer is from 10% to 60% by weight of the printable layer. Particularly preferred is that the printable layer contains both LDPE and LLDPE. In such cases, it is preferred that the top printable layer contains 40% to 80% by weight of LDPE and preferably 10% to 30% by weight of LLDPE.

[0056] More preferably, the printable layer comprises a combination of HDPE and LLDPE. Preferably, the LLDPE may be selected from LLDPE, metallocene LLDPE, or combinations thereof. Processing aids and masterbatches may also be added and are typically included in the top printable layer.

[0057] Preferably, the thickness of the printable layer accounts for 10% to 35% of the total thickness of the multilayer laminate structure.

[0058] The printable layer may have a sublayer or a single-layer structure. Preferably, when the printable layer is a single-layer structure, it comprises HDPE and LLDPE. More preferably, the single-layer structure has a thickness of 50 micrometers to 95 micrometers, preferably 85 micrometers to 95 micrometers.

[0059] Preferably, the printable layer sequentially comprises sublayers. The sublayers of the printable layer consist of an HDPE sublayer and at least one LDPE or LLDPE sublayer. More preferably, the printable layer comprises HDPE sublayers, LDPE sublayers, and LLDPE sublayers. Preferably, the printable layer may comprise at least one LLDPE sublayer, at least one HDPE and LLDPE sublayer, and at least one HDPE, LLDPE, and mLLDPE sublayer.

[0060] Preferably, the printable layer has a structure that preferably comprises at least three sublayers. The printable layer with a three-layer structure includes a top sublayer, a middle sublayer, and an inner sublayer. Preferably, when the printable layer is a multilayer structure, the printable layer is a blown film, wherein the sublayers are formed by a known extrusion method and then blown to form the film.

[0061] Preferably, the top sublayer comprises HDPE; more preferably, the top sublayer comprises HDPE and at least one of LLDPE and LDPE, and more preferably, the top sublayer comprises HDPE and LLDPE. Preferably, the LLDPE is selected from LLDPE, mLLDPE, or mixtures thereof. Furthermore, it is preferred to have a printable layer comprising a top sublayer comprising LLDPE or LDPE, preferably LLDPE. Preferably, when the multilayer laminate structure includes a metallization layer, the top sublayer comprises LLDPE and LDPE.

[0062] When the printable layer comprises a structure of at least three layers, it may include an intermediate sublayer comprising HDPE, preferably HDPE, and at least one of LLDPE or LDPE, preferably LLDPE. Furthermore, it is preferred that the printable layer includes an intermediate sublayer comprising LLDPE or LDPE, preferably LLDPE.

[0063] Most preferably, the intermediate sublayer comprises HDPE; and at least one of LLDPE or LDPE, preferably LLDPE. Preferably, the LLDPE is selected from LLDPE, mLLDPE, or mixtures thereof.

[0064] Preferably, the printable layer comprises an inner sublayer comprising LLDPE or LDPE, preferably LLDPE. Preferably, the inner sublayer may comprise HDPE and a mixture of LLDPE, LDPE, or a mixture of LLDPE and LDPE. Most preferably, the inner sublayer is LLDPE. Preferably, the LLDPE is selected from LLDPE, mLLDPE, or mixtures thereof.

[0065] Preferably, the thickness of the printable layer is in the range of 5 µm to 105 µm, more preferably 7 µm to 100 µm. Preferably, the thickness is at least 15 µm, still preferably at least 17 µm, more preferably at least 25 µm, still more preferably at least 30 µm, but preferably the thickness does not exceed 95 µm, still preferably not exceed 80 µm, still more preferably not exceed 70 µm.

[0066] Preferably, the ink layer coated on the printable layer can be deposited by any printing technology suitable for polyolefins and well known to those skilled in the art, and the printing technology is not limited to photogravure technology, flexographic technology, offset UV or EB, or digital printing.

[0067] Barrier layer: The multilayer laminated structure according to a first aspect of the invention includes a barrier layer. The barrier layer is preferably an intermediate layer and is preferably sandwiched between two layers of the multilayer laminated structure. More preferably, the barrier layer is sandwiched between the printable layer and the sealing layer.

[0068] The barrier layer preferably provides a water vapor transmission rate (WVTR) value of 0 g / mm² / day to 1 g / mm² / day or less, still preferably 0 g / mm² / day to 0.63 g / mm² / day, and more preferably 0 g / mm² / day to 0.55 g / mm² / day. The WVTR is measured using the ASTM F 1249 method. Preferably, the WVTR is in the range of 0.1 g / mm² / day to 1 g / mm² / day, preferably in the range of 0.1 g / mm² / day to 0.8 g / mm² / day, preferably in the range of 0.1 g / mm² / day to 0.63 g / mm² / day or less, still preferably in the range of 0.1 g / mm² / day to 0.55 g / mm² / day.

[0069] Preferably, the barrier layer provides an oxygen transmission rate (OTR) value of 0 to 0.4, more preferably 0 to 0.3, and even more preferably 0 to 0.25 cubic centimeters / square meter / day / 1 atm. Preferably, the OTR is in the range of 0.1 to 0.3, still preferably 0.25 to 0.3, when measured at 23°C and 0% RH. The OTR is measured using the ASTM D 3985 method.

[0070] Preferably, the thickness of the barrier layer accounts for 4% to 60% of the total thickness of the laminate, and even more preferably 4% to 20% of the total thickness of the laminate.

[0071] The barrier layer comprises ethyl vinyl alcohol as the barrier material. Preferably, the barrier layer may include additional barrier materials selected from ethylene vinyl alcohol copolymer derivatives, ceramic coatings, and mixtures thereof. More preferably, the barrier layer comprises ethylene vinyl alcohol copolymers and their derivatives. Also preferred is a multilayer structure, wherein the barrier layer comprises a combination of ethylene vinyl alcohol copolymers and / or their derivatives with a metal layer, preferably wherein the metal layer is vacuum deposited.

[0072] Preferably, the barrier layer contains less than 5% by weight of ethylene vinyl alcohol copolymer, and more preferably less than 3% by weight of ethylene vinyl alcohol copolymer.

[0073] Preferably, the barrier layer comprises an ethylene-vinyl alcohol copolymer having at least 20 mol% ethylene, still preferably at least 25 mol% ethylene, and more preferably at least 29 mol% ethylene. More preferably, the ethylene-vinyl alcohol copolymer comprises 20 mol% ethylene to less than 38 mol% ethylene, more preferably 20 mol% ethylene to less than 35 mol% ethylene, still more preferably 25 mol% ethylene to less than 35 mol% ethylene, and still more preferably 29 mol% ethylene to less than 35 mol% ethylene. Preferably, the presence of the ethylene-vinyl alcohol copolymer having 29 mol% ethylene to less than 35 mol% ethylene provides good oxygen barrier properties for the multilayer laminate structure.

[0074] Preferably, the barrier layer comprises less than 10% by weight of the total multilayer laminated structure, more preferably less than 7% by weight of the total multilayer laminated structure, and more preferably 6% by weight or less of the total multilayer laminated structure. Preferably, the barrier layer comprises from 0.5% to 10% by weight of the total multilayer laminated structure, more preferably from 0.5% to 7% by weight of the total multilayer laminated structure, and more preferably from 0.5% to 6% by weight or less of the total multilayer laminated structure.

[0075] Preferably, the barrier layer, and more preferably the EVOH sublayer, has a thickness of 6 micrometers to 15 micrometers, more preferably 8 micrometers to 15 micrometers, and even more preferably 11 micrometers to 13 micrometers.

[0076] Preferably, the barrier layer comprises HDPE. More preferably, the barrier layer comprises HDPE and at least one of MDPE and LDPE, even more preferably HDPE and at least MDPE, and even more preferably HDPE and both MDPE and LDPE. Preferably, the barrier layer does not contain LLDPE. The term "does not contain" means that no LLDPE has been added. Preferably, the barrier layer comprises 50% to 100% by weight of HDPE and at most 50% by weight of at least one of MDPE and LDPE, or both MDPE and LDPE.

[0077] Preferably, the barrier layer comprises at least three sublayers. More preferably, the barrier layer comprises three, five, or seven sublayers. Preferably, in the barrier layer, the barrier material is sandwiched between the sublayers, preferably between at least two sublayers. Preferably, the barrier layer has a barrier material sublayer sandwiched on at least one side by a sublayer containing HDPE, and still preferably, the barrier layer has a barrier material sandwiched on both sides by sublayers containing HDPE. Preferably, the HDPE sublayer comprises 75% or more HDPE by weight of the sublayer, still preferably 80% by weight, still more preferably 85% by weight, still more preferably 90% by weight, still more preferably 95% by weight, and most preferably 100% by weight.

[0078] Preferably, the barrier layer is a blown film. Preferably, when the barrier layer is a multilayer structure having 3, 5, 7 or more sublayers, it is formed by a blown film process. Preferably, the barrier layer has at least one sublayer comprising HDPE. Preferably, the barrier layer has at least one or more layers comprising MDPE.

[0079] Preferably, the barrier layer comprises a structure of at least 5 layers, including a first intermediate sub-layer, a first tie sub-layer, a barrier material sub-layer containing EVOH, a second tie sub-layer, and a second intermediate sub-layer.

[0080] More preferably, the barrier layer has a 7-layer structure. Preferably, the 7-layer structure includes a top sublayer, a first intermediate sublayer, a first connecting sublayer, a barrier material sublayer, a second connecting sublayer, a second intermediate sublayer, and an inner sublayer. As will be understood by those skilled in the art, the term "intermediate sublayer" is intended to refer to a sublayer within the barrier layer. Such intermediate sublayers may be present on either side or both sides of the EVOH-containing sublayers of the barrier layer.

[0081] Preferably, the top sublayer of the barrier layer comprises MDPE. Preferably, the top sublayer of the barrier layer comprises a copolymer of ethylene and a carboxylic acid, wherein the carboxylic acid is selected from acrylic acid, alkyl acrylate, and methacrylic acid. Preferably, the copolymer has 75% or more by weight of ethylene monomer. Also preferred is an interpolymer, which is a terpolymer of ethylene, acrylic acid or methacrylic acid, and alkyl acrylate. Preferably, the interpolymer comprises 50% to 98% by weight of ethylene. Preferably, the copolymer of ethylene and acrylic acid has a content greater than or equal to 0.925 g / cm³. 3 The density.

[0082] Preferably, the barrier layer has a barrier material sandwiched between sublayers containing HDPE on at least one side; more preferably, the barrier layer has a barrier material sandwiched between sublayers containing HDPE on both sides. Preferably, the barrier material sublayer is sandwiched between two sublayers. Preferably, the barrier layer comprises at least two sublayers containing HDPE and a barrier material sublayer, wherein the barrier material sublayer is sandwiched between the two HDPE-containing sublayers.

[0083] More preferably, the barrier material sublayer is sandwiched between a sublayer containing HDPE and at least one additional sublayer, said at least one additional sublayer containing MDPE or LDPE, more preferably at least MDPE, and even more preferably both MDPE and LDPE. Preferably, the barrier material is sandwiched between two sublayers containing HDPE and two additional sublayers, said two additional sublayers containing at least one of MDPE and LDPE, more preferably at least MDPE. Preferably, the barrier material layer includes a sublayer containing LLDPE. Preferably, the barrier material layer does not contain LLDPE.

[0084] As used in the context of this invention, the term "between" is not limited to embodiments where the HDPE-containing sublayer should be immediately adjacent to the barrier material layer. In the context of this invention, the term "between" is used to imply that the barrier material sublayer is surrounded by at least one HDPE-containing sublayer within the barrier layer. For example, the term "between" does not necessarily mean that the first intermediate sublayer and / or the second intermediate sublayer are immediately adjacent to the EVOH-containing sublayer. The first intermediate sublayer and / or the second intermediate sublayer may or may not be immediately adjacent to the EVOH-containing sublayer. As will be understood by those skilled in the art, the EVOH-containing sublayer may contain one or two connecting sublayers immediately adjacent to it on one or both sides, followed by the HDPE-containing sublayer. In other embodiments, there may even be more than two sublayers between the EVOH-containing sublayer and the HDPE-containing sublayer in the barrier layer.

[0085] Preferably, when the barrier layer has a 7-layer structure, the first intermediate sublayer preferably comprises HDPE. Preferably, the first connecting layer between the first intermediate sublayer and the barrier material sublayer comprises LDPE and a connecting material. Preferably, the second connecting sublayer located between the barrier material sublayer and the second intermediate sublayer comprises LDPE and a connecting material. Preferably, the second intermediate sublayer comprises HDPE. Preferably, the inner sublayer comprises MDPE.

[0086] Preferably, when the barrier layer comprises three sublayers, it includes a primary laminate, an intermediate barrier layer with barrier properties, and a secondary laminate. Preferably, the laminate comprises HDPE or MDPE.

[0087] Preferably, the multilayer laminate structure may have a single layer serving as both a barrier layer and a sealing layer. Preferably, the structure has an inner layer on the product side, an outer layer facing the external environment, and a connecting layer between them, wherein the inner layer serves as both a barrier layer and a sealing layer. Preferably, in such a multilayer laminate structure, the barrier material may be the innermost sublayer of the inner layer, preferably an EVOH layer. The inner layer may include additional sublayers comprising HDPE, LLDPE, LDPE, MDPE, and mixtures thereof. Preferably, the inner layer has sublayers of HDPE, LLDPE, LDPE, and MDPE, wherein the MDPE sublayer is adjacent to the EVOH sublayer. Preferably, the connecting layer comprises LDPE, and preferably the outer layer is printable, preferably comprising HDPE, more preferably a combination of HDPE and LLDPE.

[0088] Metallization layer Preferably, the barrier layer may be metallized. Preferably, the multilayer laminate structure includes a metal layer applied to the top sublayer of the barrier layer. Preferably, the top sublayer of the barrier material comprises MDPE, more preferably MDPE, and a copolymer of ethylene and a carboxylic acid selected from acrylic acid, alkyl acrylate, and methacrylic acid. Preferably, the copolymer has 75% or more by weight of ethylene monomer.

[0089] Metals that can be deposited to form the metallization layer include Al, Zn, Au, Ag, Cu, Ni, Cr, Ge, Se, Ti, Sn, or oxides thereof. In some embodiments, the metallization layer is formed of aluminum or aluminum oxide (Al₂O₃). The metallization layer may also include quasi-metallic silicon or its oxide. According to some embodiments, the metallization layer may comprise aluminum, silicon, or their oxides. More preferably, the metallization layer is an Al metal layer.

[0090] Those skilled in the art will be familiar with a variety of applicable metallization techniques. The metal layer can be applied using, but is not limited to, physical vapor deposition (e.g., vacuum vapor deposition) or chemical vapor deposition (e.g., photochemical vapor deposition). Vacuum metallization is a well-known technique for depositing metals, in which a metal source evaporates in a vacuum environment, and the metal vapor condenses on the surface of the film to form a thin layer as the film is conveyed through a vacuum chamber.

[0091] While various thicknesses are envisioned, in one or more embodiments, the metallization layer may have a thickness of no more than 100 nanometers, or preferably 10 to 80 nanometers, or still preferably 20 to 60 nanometers.

[0092] The metallization layer can advantageously provide good barrier properties against oxygen and water vapor. The combination of the barrier material sublayer and the metallization layer deposited on the designated outer surface can provide a synergistic combination of mechanical properties and barrier properties.

[0093] Preferably, the metal layer according to the invention is not a foil layer adhered to the remainder of the barrier layer by a connecting layer, wherein the term "metal foil layer" means that the layer has a thickness ranging from 6 micrometers to 15 micrometers, 6 micrometers to 12 micrometers, or 10 micrometers to 15 micrometers.

[0094] When present, the metallization layer can be sandwiched between two layers comprising a copolymer or interpolymer. Preferably, the copolymer comprises those comprising a combination of ethylene with acrylic acid, alkyl acrylate, or methacrylic acid. Preferably, the copolymer has 75% or more by weight of ethylene monomer. Also preferred is the interpolymer, which is a terpolymer of ethylene, acrylic acid or methacrylic acid, and alkyl acrylate. Preferably, the interpolymer contains 50% to 98% by weight of ethylene. Preferably, the copolymer of ethylene and acrylic acid has a content greater than or equal to 0.925 g / cm³. 3 The density.

[0095] Preferably, the barrier layer has a thickness ranging from 40 micrometers to 80 micrometers, and more preferably, the barrier layer has a thickness ranging from 40 micrometers to 60 micrometers.

[0096] Preferably, the barrier material sublayer has a thickness in the range of 10 to 13 micrometers. Preferably, the barrier material sublayer has a thickness in the range of 10 to 11 micrometers.

[0097] Preferably, the barrier layer may additionally include at least one sublayer to provide heat-sealability. The heat-sealable sublayer comprises any one selected from HDPE, MDPE, LDPE, and combinations thereof.

[0098] sealing layer The multilayer structure preferably includes a sealing layer. The sealing layer can typically be heated and pressed to seal two multilayer structures or portions of the multilayer structure to each other. As used herein, the term "sealing layer" refers to a multilayer polyolefin and means a layer typically present on the inside of a packaging film to heat-seal and wet-seal the contents of the packaged product.

[0099] Preferably, the sealing film is laminated to the barrier film by an extruded layer extruded in the shape of a film. Thus, the extruded layer acts as an adhesive to form the top sealing layer and the barrier layer of the multilayer laminated structure. The extruded layer preferably comprises LDPE.

[0100] Preferably, the sealing layer is a blown film. Preferably, when the sealing layer is a multilayer structure having 3, 5, 7 or more sublayers, it is formed by a blown film process.

[0101] Preferably, the sealing layer forms the innermost layer of the laminated tube and is in contact with the product, i.e., the toothpaste composition. The sealing layer preferably comprises polyethylene having a heat-sealing initiation temperature of 95°C or lower. For example, the sealing layer may comprise polyethylene having a heat-sealing initiation temperature of 92.5°C or lower, 90°C or lower, 87.5°C or lower, 85°C or lower, 82.5°C or lower, 80°C or lower, 75°C or lower, or even 70°C or lower.

[0102] Preferably, the sealing layer comprises HDPE. Still preferably, the sealing layer comprises HDPE and at least one of MDPE, LDPE, or LLDPE. Still more preferably, the sealing layer comprises HDPE, MDPE, and LLDPE.

[0103] Preferably, the sealing layer can be a multi-layer structure. Preferably, the sealing layer comprises a top sealing sublayer, a middle sealing sublayer, and an inner sealing sublayer. Based on the total thickness of the sealing layer, the sealing layer may preferably contain about 12% to 55% MDPE. Based on the total thickness of the sealing layer, the sealing layer may preferably contain 10% to 45% HDPE. Based on the total thickness of the sealing layer, the sealing layer may preferably contain 5% to 22% LLDPE. Based on the total thickness of the sealing layer, the sealing layer may preferably contain 0% to 35% LDPE.

[0104] Preferably, the sealing layer is multi-layered, having 3 to 7 layers. Preferably, the sealing layer has a thickness of 40 to 80 micrometers, still preferably in the range of 50 to 60 micrometers.

[0105] Connection layer: Preferably, the barrier layer may include one or more connecting layers. The term "connecting layer" refers to a layer that bonds any two layers with different polarities. Preferably, the connecting layer may contain a connecting material.

[0106] Preferably, the connecting material comprises a modified polyolefin. Preferably, the modified polyolefin is based on an ethylene polymer or a propylene polymer. Preferably, the connecting material comprises a modified polyolefin selected from maleic acid-modified polyethylene, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, anhydride-grafted ethylene / 1-butene copolymer, anhydride-grafted ethylene / 1-hexene copolymer, polyethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, anhydride-grafted ethylene / 1-octene copolymer, maleic acid-modified polyethylene, and maleic anhydride-grafted polyethylene. Preferably, the connecting material comprises those selected from maleic acid-modified polyethylene and maleic anhydride-grafted polyethylene, and still preferably comprises maleic anhydride-grafted polyethylene.

[0107] Preferably, the connecting material is selected from maleic anhydride-grafted polyethylene, copolymers of ethylene and carboxylic acids, or combinations thereof. As used herein, "maleic anhydride-grafted" refers to a substance containing a salt or ester of maleic acid. More preferably, the connecting layer is maleic anhydride-grafted polyethylene, preferably maleic anhydride-grafted linear low-density polyethylene. Suitable commercially available examples of maleic anhydride-grafted polyethylene include Bynel from Dow. TM 41E687B. Preferably, the connecting layer comprises a connecting material and LDPE.

[0108] Preferably, the connecting layer comprises 3% by weight or less maleic anhydride-grafted polyethylene.

[0109] Extruded layer: The term "extruded layer" refers to a layer through which a blown film is bonded together by molten resin extruded between two films in the shape of a film to form the multilayer laminated structure. The molten resin serves as a binder. For example, the sealing layer and the barrier layer are attached / laminated via the extruded layer. Preferably, the extruded layer comprises a polyolefin, a polyolefin copolymer, or a combination thereof. Preferably, the copolymer is selected from ethylene-acrylic acid polymers. Preferably, the extruded layer comprises a polymer of ethylene, or a copolymer of ethylene and a carboxylic acid (preferably acrylic acid).

[0110] Preferably, the extruded layer comprises 50% to 100% by weight of LDPE, more preferably 80% to 100% by weight of LDPE, and still preferably 100% by weight of LDPE. Preferably, the extruded layer comprises LDPE and ethylene acetate acrylate (EAA), and more preferably, when the barrier layer comprises a metallized coating, the extruded layer between the top printable layer and the barrier layer comprises a mixture of LDPE and ethylene acetate acrylate (EAA).

[0111] Preferably, the extruded layer between the barrier layer and the sealing layer comprises 50% to 100% LDPE, more preferably 80% to 100% LDPE, and still preferably 100% LDPE.

[0112] Preferably, the extruded layer is a single layer of polyethylene or polyethylene blended with the copolymer, or a co-extruded layer of ethylene-acrylic acid copolymer and polyethylene.

[0113] Preferably, the extruded layer has a thickness ranging from 10 micrometers to 30 micrometers, more preferably from 15 micrometers to 25 micrometers.

[0114] Recycled polyethylene: Preferably, the flexible laminated pipe according to the invention may comprise recycled polyethylene. The recyclable pipe may preferably contain at least 50% by weight HDPE.

[0115] Preferably, the flexible laminated tube comprises 15% to 70% by weight of post-consumption recycled (PCR) polyethylene. Preferably, the flexible laminated tube comprises 30% to 85% by weight of virgin (PCR) polyethylene.

[0116] Preferably, the shoulder portion of the flexible laminate contains at least 50% by weight HDPE. The HDPE in the shoulder portion of the flexible laminate can be virgin HPDE, recycled HDPE, or a mixture thereof. Preferably, the shoulder portion of the flexible laminate contains 50% to 100% by weight HDPE, more preferably 70% to 100% by weight HDPE, and still more preferably 85% to 100% by weight HDPE.

[0117] Suitable recycled HDPE has a melt flow rate of less than 1 g / min.

[0118] Preferably, the recycled HDPE is added to an intermediate layer of the barrier layer that is not in direct contact with other layers. Preferably, the first intermediate sublayer and / or the second intermediate sublayer of the barrier layer contains recycled HDPE.

[0119] Preferably, the total thickness of the laminate is in the range of 50 µm to 350 µm, more preferably in the range of 175 µm to 350 µm, and even more preferably in the range of 50 µm to 300 µm. More preferably, it is in the range of 60 µm to 250 µm, and even more preferably in the range of 70 µm to 150 µm. The range of 50 µm to 300 µm is generally suitable for laminates that can be used to manufacture foldable tubes.

[0120] In a preferred embodiment of the present invention, a multilayer laminated structure is provided, comprising: (i) At least one printable layer; (ii) First extruded layer; (iii) At least one barrier layer; (iv) Second extruded layer; and, (v) At least one sealing layer.

[0121] In a preferred embodiment of the present invention, a three-layer multilayer laminated structure is provided, comprising: (i) At least one printable layer; (ii) Extruded layer; and, (iii) At least one barrier layer, wherein the at least one barrier layer preferably comprises a sealing sublayer.

[0122] Preferably, in the multilayer laminated structure according to the first aspect of the invention, there is no adhesive system. Preferably, in the multilayer laminated structure according to the first aspect of the invention, there is no adhesive system between the top printable layer and the barrier layer. Preferably, in the multilayer laminated structure according to the first aspect of the invention, there is no adhesive system between the barrier layer and the sealing layer.

[0123] Preferably, the multilayer laminated structure according to the first aspect of the invention has a thickness in the range of 170 micrometers to 220 micrometers.

[0124] In another preferred embodiment of the invention, the multilayer laminate structure includes a top printable layer, a bottom sealing layer, and an intermediate barrier layer therebetween, wherein: i) The top printable layer comprises HDPE, and preferably at least one of LDPE or LLDPE; ii) The sealing layer comprises polyethylene, wherein the polyethylene comprises HDPE; and, iii) The intermediate barrier layer is extruded and laminated onto the printable layer and the sealing layer.

[0125] Preferably, the top printable layer comprises HDPE and at least one of LDPE or LLDPE, wherein the HDPE content in the layer is 10 to 60% by weight. Preferably, the top printable layer comprises LDPE and LLDPE. Preferably, the top printable layer comprises 40% to 80% by weight of LDPE and 10% to 30% by weight of LLDPE. Preferably, the top printable layer accounts for 10% to 35% by weight of the total thickness of the laminate. Preferably, the top printable layer does not contain MDPE. More preferably, the HDPE content in the printable layer is 25% to 60% by weight.

[0126] Preferably, the sealing layer comprises HDPE and at least one of LDPE, LLDPE, or MDPE. More preferably, the sealing layer comprises HDPE, LLDPE, and MDPE, or comprises HDPE, LDPE, and MDPE. Preferably, the sealing layer accounts for 10% to 35% by weight of the total thickness of the laminate.

[0127] In one aspect, the sealing layer comprises HDPE, wherein the HDPE content in the layer is 5% to 80% by weight, preferably 5% to 20% by weight, more preferably 5% to 15% by weight, and even more preferably 8% to 12% by weight.

[0128] Preferably, the barrier layer comprises at least one of HDPE and MDPE or LDPE, more preferably HDPE and MDPE, and still preferably HDPE, MDPE and LDPE. Preferably, the barrier layer accounts for 20% to 60% by weight of the total thickness of the laminate. Preferably, the barrier layer is a multilayer structure comprising at least two sublayers containing HDPE and a barrier material sublayer, wherein the barrier material sublayer is sandwiched between the two HDPE sublayers.

[0129] Optional components present in the multilayer laminated structure: Preferably, the multilayer laminated structure may include suitable additives, such as stabilizers, neutralizers, lubricants, or antioxidants. In principle, additives used for polyolefins (e.g., polyethylene or polypropylene) are also suitable for cyclic olefin polymer films. Examples of usable UV stabilizers are absorbers such as hydroxyphenylbenzotriazole, hydroxybenzophenone, formamidinium, or benzylidene camphor; quenchers such as cinnamate esters or nickel chelates; free radical scavengers such as sterically hindered phenols; hydroperoxide scavengers such as nickel or zinc complexes of sulfur-containing compounds; or light stabilizers; and mixtures thereof. Examples of suitable lubricants include fatty acids and esters, amides and their salts; silicones or waxes such as polypropylene wax or polyethylene wax. Examples of antioxidants that can be added are: free radical scavengers such as substituted phenols and aromatic amines; and / or peroxide scavengers such as phosphites / salts, phosphate esters / salts, and thiolated compounds.

[0130] additive: Preferably, the multilayer laminated structure according to the invention comprises additives. Preferably, the additives may be selected from colorants, coloring masterbatches, TiO2 masterbatches, slip agents, anti-caking agents, anti-fogging agents, UV blocking additives, and mixtures thereof. Preferably, the total amount of the additives is 1 to 20% by weight based on the sublayers.

[0131] Preferably, the multilayer laminated structure may include a colorant masterbatch. The colorant masterbatch refers to a mixture in which pigments are dispersed at a high concentration in a carrier material, or dyes are dissolved at a high concentration in a carrier material. The colorant masterbatch is used to impart color to the final product. The carrier material may be polyethylene, more preferably HDPE, LDPE, LLDPE, and mixtures thereof. The pigment may preferably be selected from inorganic pigments, organic pigments or dyes, polymer resins, and mixtures thereof. Non-limiting examples of pigments include titanium dioxide (e.g., rutile, anatase), copper phthalocyanine, antimony oxide, zinc oxide, calcium carbonate, fumed silica, phthalocyanine (e.g., phthalocyanine blue), ultramarine blue, cobalt blue, monoazo pigments, diazo pigments, acid dyes, basic dyes, quinacridones, and / or mixtures thereof.

[0132] Method for preparing the multilayer laminated structure: The method for preparing the multilayer laminated structure as described herein includes the following steps: (i) Obtaining at least one membrane by means of the following steps: a. Melting the at least one polyethylene to obtain a polyethylene melt stream; b. Extruding the polyethylene melt from an annular die in an upward or downward flow to obtain extruded material; c. Expand the extruded material to obtain a blown film bubble; and d. Quench the blown film bubble with chilled water to obtain the film; (ii) Obtaining at least one extruded laminated polymer; and (iii) At least two films are laminated by extruding the extruded laminated polymer between the at least two films to obtain a multilayer laminated structure.

[0133] Extrusion is one of the most widely used methods for producing films and tubes from polyethylene. To manufacture a film, a blown film process is used, and it begins by feeding plastic material from a hopper into an extruder, where the plastic material is heated to form a melt. This molten plastic is forced through a circular-shaped die, resulting in a semi-solid tube whose diameter is expanded by blowing air through the die. The film is cooled using either air or water to allow it to crystallize. Further, several pressure rollers flatten it to form a roll of sheet material. The film can be extruded in an upward, downward, and horizontal direction, and the extrusion and blown film rates can be controlled to achieve the desired properties of the extruded film.

[0134] toothpaste composition According to a first aspect of the invention, a toothpaste composition comprising a fragrance is provided.

[0135] The term "toothpaste" refers to an oral composition used to clean the surfaces of the oral cavity. Such compositions are not intended to be swallowed for the purpose of systemic administration of therapeutic agents, but are applied to the oral cavity for treatment and then spat out. Typically, such compositions are used in conjunction with cleaning tools such as toothbrushes, usually by applying them to the bristles of the toothbrush and then brushing the accessible surfaces of the oral cavity.

[0136] The toothpaste composition may be in the form of a viscous material, preferably in the form of a squeezeable semi-solid. Still preferably, the toothpaste composition may be in the form of a cream product, a gel product, or a paste product (or mixtures thereof). The term "toothpaste composition" according to the invention more preferably covers gel or paste forms.

[0137] The toothpaste composition may be a single-phase composition or a combination of two or more separate toothpaste compositions. The toothpaste composition may be in any desired form, such as deep stripes, surface stripes, multilayers, a gel form with an surrounding paste, or any combination thereof. Each toothpaste composition, including two or more separate toothpaste compositions, may be contained in physically separated compartments of the dispenser and dispensed side-by-side.

[0138] spices: The toothpaste composition according to a first aspect of the invention comprises a fragrance. The fragrance preferably enhances the flavor of the composition.

[0139] Any oral-acceptable natural or synthetic flavoring can be used, including but not limited to tea flavoring, vanillin, sage, marjoram, parsley oil, spearmint oil, cinnamon oil, wintergreen oil (methyl salicylate), peppermint oil, clove oil, laurel oil, anise oil, eucalyptus oil, citrus oil, fruit oils, and flavorings, including those derived from lemon, orange, lime, grapefruit, apricot, banana, grape, apple, strawberry, cherry, pineapple, etc., flavorings derived from legumes, and flavorings derived from nuts, such as coffee, cocoa, kola nut, peanut, almond, etc. Also preferred are 1-menthol acetate, ethyl vanillin, piperaldehyde, 4-cis-heptenal, diacetyl, methyl-p-tert-butylphenylacetate, and mixtures thereof. Preferably, the flavoring is in an adsorbed form, an encapsulated form, or a mixture thereof.

[0140] The flavorings described in this article also include ingredients that provide aroma and / or other sensory effects in the mouth, including cooling or warming effects. Examples of such ingredients include menthol, menthol acetate, menthol lactate, camphor, eucalyptol, eucalyptol, anethole, eugenol, cassia seed, methyl salicylate, oxanone, α-ionone, propenyl guaiacol, thymol, linalool, benzaldehyde, cinnamaldehyde, N-ethyl-p-menthane-3-carboxamide, N,2,3-trimethyl-2-isopropylbutyramide, 3-(1-menthoxy)-propane-1,2-diol, cinnamaldehyde glycerol acetal (CGA), menthone glycerol acetal (MGA), etc. One or more flavorings are optionally present in a total amount of about 0.01% to about 5% by weight, more preferably 0.03% to 2.5% by weight, still preferably 0.05% to 1.5% by weight, and even more preferably 0.1% to about 0.3% by weight, of the total weight of the composition. A preferred coolant is a menthol carboxamide reagent, such as N-ethyl-p-menthol-3-carboxamide (commercially known as "WS-3"). ® Menthyl carbamoyl aminoethyl acetate (commercially known as "WS-5") ® The flavoring is typically present in 0.001 to 5% by weight, more preferably 0.1 to 5% by weight, still more preferably 0.1 to 3% by weight, further preferably 0.1 to 2.5% by weight, still preferably 0.1 to 1.5% by weight, based on the weight of the composition.

[0141] Bicarbonate: Preferably, the toothpaste composition contains a bicarbonate. Any orally acceptable bicarbonate can be used, including but not limited to alkali metal bicarbonates, such as sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, etc. The bicarbonate is present in a total amount of 0.1% to 50% by weight, preferably 0.1% to 20% by weight, and more preferably 0.1% to 5% by weight of the total weight of the composition.

[0142] Sodium salt Preferably, the toothpaste composition comprises a sodium salt. Preferably, the sodium salt is selected from sodium chloride, sodium carbonate, and mixtures thereof.

[0143] water Preferably, the toothpaste composition contains 15% to 34.5% water by weight, based on the weight of the toothpaste composition.

[0144] In some embodiments, the water content is at least 35% by weight, still preferably 35% to 55% by weight, more preferably 35% to 50% by weight, still preferably 35% to 45% by weight, and more preferably 38% to 45% by weight, based on the total weight of the composition.

[0145] More preferably, the toothpaste composition contains 5% to 60% by weight of an abrasive. More preferably, the toothpaste composition contains a surfactant.

[0146] In addition to the ingredients specified above, the compositions according to the invention typically contain additional ingredients for enhancing performance and / or consumer acceptability.

[0147] Friction agent: Toothpaste typically contains abrasives, preferably silica-based, calcium-based, or mixtures thereof. Gel-form toothpaste compositions generally contain silica-based abrasives; however, opaque pastes typically contain calcium-based abrasives, particularly chalk. The amount of abrasive needs to be controlled, as excessive abrasive leads to increased abrasion. Furthermore, an uncontrolled amount of abrasive will adversely affect the viscosity of the toothpaste.

[0148] Preferably, the composition according to the invention may include one or more particulate abrasive materials selected from, but not limited to, silica, alumina, calcium carbonate, dicalcium phosphate, calcium pyrophosphate, hydroxyapatite, trimetaphosphate, and insoluble hexametaphosphate, including agglomerated particulate abrasive materials, typically in an amount ranging from 3% to 60% by weight based on the weight of the toothpaste composition.

[0149] Preferred toothpaste compositions contain 10% to 60% by weight, more preferably 30% to 50% by weight, and most preferably 30% to 45% by weight of an abrasive, wherein the abrasive is preferably a calcium-based abrasive.

[0150] Preferred toothpaste compositions contain calcium-based abrasives. Particularly preferred abrasives are finely ground natural chalk (FGNC), obtained from limestone or marble. FGNC can also be chemically or physically modified by coating during or after grinding through heat treatment. Typical coating materials include magnesium stearate and magnesium oleate. The morphology of FGNC can also be modified during the grinding process using different grinding techniques, such as ball milling, air classifying milling, or spiral jet milling. FGNC can be used as the sole calcium-containing abrasive. However, FGNC can also be used in combination with other calcium-containing abrasives to balance wear.

[0151] Other preferred calcium-based abrasives include dicalcium phosphate (DCP), calcium pyrophosphate, and precipitated calcium carbonate (PCC).

[0152] When using a combination of calcium-based abrasives, it is preferred that FGNC constitutes 35 to 100% of the total content of the calcium-based abrasive, more preferably 75 to 100%, and particularly 95 to 100%. In such cases, the balance is most preferably PCC.

[0153] Other abrasives may also be used depending on the expected level of abrasion and the composition of the toothpaste. These include synthetic abrasives such as amorphous precipitated silica and silica gel. Other abrasives include magnesium carbonate, sodium metaphosphate, potassium metaphosphate, zirconium silicate, potassium metaphosphate, magnesium orthophosphate, tricalcium phosphate, magnesium orthophosphate, trimagnesium phosphate, aluminum silicate, zirconium silicate, and perlite.

[0154] The toothpaste composition may preferably contain a silica-based abrasive. Preferred abrasive silica used in this invention is silica with a low refractive index. It can be used as the sole abrasive silica or in combination with other abrasive silicas having low levels (e.g., those according to EP 236070). Typical examples of suitable low-refractive-index abrasive silicas (e.g., having an RI between 1.435 and 1.445) are Tixosil 63 and 73 from Rhone Poulenc; Sident 10 from Degussa; Zeodent 113 from Zeofinn; Zeodent 124 from Huber; and Sorbosil AC 77 from Crosfield Chemicals (having an RI of about 1.440). These silicas are typically present in amounts of 5 to 60% by weight in the total composition, and typically from 5% to 20% by weight.

[0155] Preferred toothpaste compositions based on silica abrasives contain 3% to 20% by weight, more preferably 5% to 18% by weight, and most preferably 5% to 15% by weight of an abrasive. Also preferred are low-abrasive toothpaste compositions having reduced levels of silica-based abrasives, wherein the silica-based abrasive is present in an amount ranging from 4% to 10% by weight, still preferably from 4% to 9% by weight, and still more preferably from 4% to 8% by weight.

[0156] In some embodiments, the toothpaste composition may have a silica-based abrasive as the sole abrasive. Such compositions are typically in gel form.

[0157] Surfactants: Preferably, the toothpaste composition contains a surfactant, which is also commonly referred to as a foaming agent. Suitable surfactants are those that are relatively stable and provide foam over a wide pH range. Preferably, the surfactant may be selected from anionic surfactants, amphoteric surfactants, nonionic surfactants, or mixtures thereof.

[0158] Preferably, the surfactant is anionic. Anionic surfactants that can be used herein include water-soluble salts of alkyl sulfates having 8 to 20 carbon atoms in the alkyl group (e.g., sodium alkyl sulfate) and water-soluble salts of sulfonated monoglycerides of fatty acids having 8 to 20 carbon atoms, sarcosinates, taurines, and mixtures thereof. Sodium lauryl sulfate and sodium coconut monoglyceride sulfonate, sodium lauryl sarcosinate, sodium lauryl hydroxyethyl sulfonate, sodium laureth carboxylate, and sodium dodecylbenzene sulfonate are examples of such anionic surfactants.

[0159] The preferred composition contains 0.25% to 12% by weight, more preferably 0.5% to 8% by weight, and most preferably 1% to about 6% by weight of anionic surfactant.

[0160] Some anionic surfactants, particularly sodium lauryl sulfate, possess antibacterial properties. These properties provide a degree of immediate antibacterial activity; however, this effect is typically very short-lived.

[0161] Other surfactants, such as nonionic surfactants, amphoteric surfactants, or zwitterionic surfactants, may also be included.

[0162] Nonionic surfactants can be broadly defined as compounds resulting from the condensation of an oxidized alkenyl group (which is inherently hydrophilic) with an organic hydrophobic compound that may be aliphatic or alkyl aromatic in nature. Examples of suitable nonionic surfactants include, but are not limited to, alkyl polyglucosides, poloxamer (trade name PLURONIC). ® Sales), polyoxyethylene, polyoxyethylene dehydrated sorbitol ester (under the trade name TWEENS) ® Sales), POLYOXYL ® Hydrogenated castor oil (40%), fatty alcohol ethoxylates, alkylphenol polyoxyethylene condensates, products derived from the condensation of ethylene oxide with propylene oxide and ethylenediamine, aliphatic alcohol ethylene oxide condensates, long-chain tertiary amine oxides, long-chain tertiary phosphine oxides, long-chain dialkyl sulfoxides, and mixtures of such materials. Preferably, the alkyl polyglucosides comprise those of formula C... n H 2n+1 O(C6H 10 O5) x The H-characterized components, wherein n has a value of 12 to 22, more preferably 12 to 16, and the degree of polymerization (x) is 1 to 20, still preferably 1 to 10, more preferably 1 to 2, still more preferably 1 to 1.4. Preferably, the alkyl polyglucoside is added to the toothpaste composition in an amount ranging from 0.1% to 2% by weight.

[0163] Available amphoteric surfactants can be broadly described as derivatives of aliphatic secondary and tertiary amines, wherein the aliphatic group is linear or branched, and wherein one of the aliphatic substituents contains about 8 to about 18 carbon atoms, and one contains an anionic water-solubilizing group, such as a carboxylate, sulfonate, sulfate, phosphate, or phosphonate group. Other suitable amphoteric surfactants are betaines, particularly cocoaminopropyl betaine. Mixtures of amphoteric surfactants may also be used. Betaines may also be used; a suitable example is cocoaminopropyl betaine.

[0164] One or more surfactants are optionally present in a total amount of about 0.01% to about 10% by weight based on the total weight of the composition, more preferably in an amount ranging from 0.05% to about 5% by weight, or from 0.1% to about 3% by weight.

[0165] Foam regulator: The toothpaste composition according to the invention may preferably contain at least one foam modifier, for example, which can be used to increase the amount, thickness, or stability of foam produced by the composition upon stirring. Any orally acceptable foam modifier may be used, including but not limited to polyethylene glycol (PEG), also known as polyethylene oxide. High molecular weight PEG is suitable, including those having an average molecular weight of 200,000 to 7,000,000, for example 500,000 to 5,000,000, or 1,000,000 to 2,500,000. One or more PEGs are optionally present in a total amount of about 0.1% to about 10% by weight, for example about 0.2% to about 5% by weight, or about 0.25% to 5% by weight.

[0166] Bipolar antimicrobial particles: Preferred toothpaste compositions contain 0.1% to 10% by weight, more preferably 0.5% to 5% by weight, of bipolar antimicrobial particles. More preferably, such particles contain a loading of 1% to 60% by weight of a quaternary ammonium antimicrobial agent. A particularly preferred quaternary ammonium antimicrobial agent is cetylpyridinium chloride.

[0167] Thickened silica: Preferably, the toothpaste composition comprises an inorganic thickener. Preferably, the inorganic thickener comprises thickening silica. Preferably, based on the total weight of the composition, the toothpaste composition comprises 1 to 6% by weight; still preferably 2 to 5% by weight; still more preferably, and even more preferably 3 to 5% by weight of thickening silica. Examples of thickening silica that can be used are Zeodent 165, Zeodent 163, and Zeodent 153 (from Huber); Aerosil ® 200 and Sident ® 22S (from Evonik); Sylodent ® 15 and Perkasil ® SM 660 (from WR Grace & Co.); and Tixocil43B (from Rhodia).

[0168] Preferably, the thickening silica may also be present in a lower amount of 0 to 2% by weight of the toothpaste composition. Conventional gel toothpastes typically contain up to 8.5% by weight of thickening silica, while opaque toothpastes typically contain 4% to 10% by weight of thickening silica. The toothpaste composition may preferably contain up to 2% by weight of thickening silica. Preferred compositions have 1.5% by weight or even less than 1% by weight of thickening silica. The most preferred compositions have less than 0.5% by weight of thickening silica. Highly preferred compositions are silica-free.

[0169] When present, preferred thickening silica includes AEROSIL from Degussa. ® T series or CAB-O-SIL from Cabot Corporation ® Series, silicone (e.g., SYLODENT from WR Grace & Co.) ® Or SYLOX ® (Series) or precipitated silica (e.g., ZEOTHIX from JM Huber Corporation) ® 265). Other available silica thickeners include ZEODENT. ® 165. ZEODENT ® 163 and / or 167 and ZEOFREE ® 153, 177, and / or 265 silica are all available from JM Huber Corporation. Other preferred thickening silicas include MFIL. ® MFIL ® -P (from Madhu Silica), SIDENT ® 22 S and AEROSIL ® 200 (from Evonik Industries), SYLODENT from WRGrace & Company ® and PERKASIL ® Thickened silica and Tixosil from Rhodia ® 43 and 331, synthetic finely broken pyrolytic silica, for example, under the trademark SYLOID ® 244, SYLOID ® 266 and AEROSIL ® Those that were sold as D-200s.

[0170] Moisturizer: Toothpaste compositions preferably contain humectants. Humectants are typically included in toothpaste to achieve a soft and smooth texture. Humectants also reduce the tendency of toothpaste to lose moisture.

[0171] The toothpaste composition preferably contains 0% to 70% by weight of a humectant, or 3.5% to 70% by weight of a humectant. More preferably, the toothpaste composition has 10% to 40% by weight, and more particularly 10% to 20% by weight of a humectant.

[0172] Preferably, when the toothpaste composition is a silica-based gel composition, the amount of the humectant is 40% to 70% by weight, more preferably 40% to 66% by weight, based on the weight of the toothpaste composition.

[0173] Preferably, when the toothpaste composition is a chalk-based composition, the amount of the humectant is 5% to 30% by weight, more preferably 10% to 25% by weight, and still preferably 10% to 20% by weight, based on the weight of the toothpaste composition.

[0174] A particularly preferred humectant is sorbitol, which is typically available in the form of a 70% aqueous solution. When the humectant is supplied in aqueous solution form, for example, sorbitol as a 70% by weight aqueous solution, the amount of the humectant is calculated based on the weight of the active ingredient of the humectant; for example, for a composition containing 25% by weight of sorbitol (as a 70% by weight aqueous solution), the concentration of the humectant is 17.5% by weight.

[0175] Other preferred humectants include glycerin, maltitol, and xylitol. More preferred toothpastes contain glycerin and sorbitol to achieve a smooth mouthfeel, but their cumulative levels should not exceed the disclosed upper limits.

[0176] Adhesive: The toothpaste composition preferably includes a binder. A preferred toothpaste composition has a binder that provides a good structure to the paste. Cellulose binders are particularly preferred. Preferred cellulose-based binders include cellulose ethers, such as hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), ethyl hydroxyethyl cellulose (EHEC), carboxymethyl cellulose (CMC), carboxymethyl hydroxyethyl cellulose (CMHEC), hydroxypropyl hydroxyethyl cellulose (HPHEC), methylcellulose (MC), methyl hydroxypropyl cellulose (MHPC), methyl hydroxyethyl cellulose (MHEC), carboxymethyl methyl cellulose (CMMC), hydrophobically modified carboxymethyl cellulose (HMCMC), hydrophobically modified hydroxyethyl cellulose (HMHEC), hydrophobically modified hydroxypropyl cellulose (HMHPC), hydrophobically modified ethyl hydroxyethyl cellulose (HMEHEC), hydrophobically modified carboxymethyl hydroxyethyl cellulose (HMCMHEC), hydrophobically modified hydroxypropyl hydroxyethyl cellulose (HMHPHEC), hydrophobically modified methylcellulose (HMMC), hydrophobically modified methyl hydroxypropyl cellulose (HMMHPC), hydrophobically modified methyl hydroxyethyl cellulose (HMMHEC), and hydrophobically modified carboxymethyl methyl cellulose (HMCMMC).

[0177] Other cellulosic binders include cationic hydroxyethyl cellulose (cationic HEC), cationic hydrophobically modified hydroxyethyl cellulose (cationic HMHEC), and microcrystalline cellulose.

[0178] A highly preferred binder is sodium carboxymethyl cellulose (SCMC). Particularly preferred sodium carboxymethyl cellulose includes those having a degree of substitution of 0.6 to 1.2 (i.e., 6 to 12 hydroxyl groups are replaced by carboxymethyl for every 10 dehydrated glucose units), 0.6 to 0.99, and preferably 0.7 to 0.95.

[0179] Guar gum or its derivatives can be used in addition to, or as a substitute for, cellulose-based binders; however, such binders are less preferred than cellulose-based binders. These derivatives include carboxymethyl guar gum (CM guar gum), hydroxyethyl guar gum (HE guar gum), hydroxypropyl guar gum (HP guar gum), carboxymethyl hydroxypropyl guar gum (CMHP guar gum), cationic guar gum, hydrophobically modified guar gum (HM guar gum), hydrophobically modified carboxymethyl guar gum (HMCM guar gum), hydrophobically modified hydroxyethyl guar gum (HMHE guar gum), hydrophobically modified hydroxypropyl guar gum (HMHP guar gum), cationic hydrophobically modified hydroxypropyl guar gum (cationic HMHP guar gum), hydrophobically modified carboxymethyl hydroxypropyl guar gum (HMCMHP guar gum), and hydrophobically modified cationic guar gum (HM cationic guar gum).

[0180] Other less preferred gums include xanthan gum, carrageenan gum and its derivatives (e.g., Irish moss and viscarin), gellan gum, sclerotium gum and its derivatives, amylopectin, rhamsan gum, welan gum, konjac, gel polysaccharides, alginate, alginic acid, alginate and its derivatives, starch phosphate derivatives, agar and its derivatives, gum arabic and its derivatives, pectin and its derivatives, chitosan and its derivatives, guilarin gum, locust bean gum, natto gum, tragacanth gum, chitin derivatives, gelatin, β-glucan, dextrin, dextran, cyclodextrin and polyquaternium salts, furceleren gum, ghatti gum, psyllium gum, quince gum, tamarind gum, larch gum and tara gum.

[0181] Other thickeners: Preferred toothpaste compositions may also include one or more other thickeners, such as carboxyvinyl polymers, including those derived from BF Goodrich using CARBOPOL. ® A range of commercially available carbomers, including CARBOPOL ® 934, 940, 941, and 956. Other preferred grades include acrylate / C. 10-30 Alkyl acrylate crosslinked polymer, which is from Noveon Corporation with ULTREZ ® 21. PEMULEN ® TR-1 and PEMULEN ® TR-2 is commercially available. Preferred compositions may contain 0.05 to 10% by weight, more preferably 0.1 to 5% by weight, or even more preferably 0.25 to 4% by weight of other thickeners.

[0182] Preferably, the toothpaste composition may further comprise a preservative, such as benzyl alcohol or parabens, such as methylparaben and propylparaben. In some embodiments, the preservative is benzyl alcohol. Based on the total weight of the composition, the preservative may be present in the composition in an amount of 0.1 to 1% by weight; 0.2 to 0.5% by weight; or about 0.3% by weight.

[0183] Desensitizing agents: The desensitizing agent is a potassium salt selected from potassium nitrate, potassium chloride, potassium citrate, potassium tartrate and potassium acetate, preferably used in an amount of 0.5 to 3% by weight, more preferably 1 to 2.5% by weight, and particularly 1.7 to 2.2% by weight.

[0184] Silicates: Preferred toothpaste compositions may contain alkali metal silicates. The alkali metal is sodium or potassium, preferably sodium. Sodium silicate is typically obtained as a 10-40% aqueous solution, most commonly a 30% solution. Sodium silicate can be obtained as neutral or basic sodium silicate. Preferred toothpastes contain neutral sodium silicate. Sodium silicate can be obtained in different Na₂O:SiO₂ ratios.

[0185] Sodium silicate having a Na₂O:SiO₂ ratio in the range of 3.0 to 3.8 is preferred, with a more highly preferred range of 3.25 to 3.5. Preferred toothpastes contain 0.1 to 5% by weight of silicate (based on dry weight). Therefore, a 30% sodium silicate solution is added to the composition in an amount ranging from 0.3% to 3% by weight.

[0186] Anti-caries agents: Preferred compositions may include one or more anti-caries agents. Such agents are typically fluorides.

[0187] As used herein, the term "fluoride source" refers to a source of free fluoride ions and / or monofluorophosphate ions. Non-limiting examples of fluoride ion sources include sodium monofluorophosphate, ammonium monofluorophosphate, stannous fluoride, sodium fluoride, and ammonium fluoride. Other preferred caries inhibitors include amine fluorides, sodium trimetaphosphate, and casein. Highly preferred is that the fluoride source is an alkali metal salt of monofluorophosphate, preferably sodium monofluorophosphate (SMFP).

[0188] When toothpaste compositions involve calcium-based abrasives (particularly chalk), sodium fluoride phosphate (SMFP) is the preferred fluoride source because sodium fluoride reacts with calcium carbonate to form insoluble calcium fluoride with limited anti-mite activity. Preferred compositions contain 0.01% to 2% by weight, more preferably 0.15% to 1% by weight, and particularly preferably 0.2% to 0.5% by weight of a caries antagonist. It is preferred to maintain a free fluoride ion concentration of 100 to 2000 ppm, preferably 900 to 1500 ppm. Other preferred caries antagonists include sodium fluoride and stannous fluoride, amine fluoride, sodium trimetaphosphate and casein, and mixtures thereof. Most preferably, the fluoride source is sodium fluoride and sodium monofluorophosphate (SMFP).

[0189] The fluorine source may preferably be added to the composition at a level of about 0.001 wt% to about 10 wt%, for example, about 0.003 wt% to about 5 wt%, 0.01 wt% to about 1 wt%, or about 0.05 wt%. In some embodiments, the stannous fluoride is present in an amount of 0.1 wt% to 2 wt% (0.1 wt% to 0.6 wt%) based on the total composition. However, it should be understood that the weight of the fluoride salt providing an appropriate level of fluoride ions will obviously vary based on the weight of the counterion in the salt, and such amounts can be readily determined by those skilled in the art. In some embodiments, the fluorine source is a fluoride salt (e.g., sodium fluoride (e.g., about 0.32 wt%)) present in an amount of 0.1 wt% to 2 wt% (0.1 wt% to 0.6 wt%) based on the total composition.

[0190] Other antibacterial agents: Additional antimicrobial agents may be present in the composition, although they are not strictly necessary. Examples include triclosan and other halogenated bisphenol compounds, such as 2,2'-methylenedi-(4-chloro-6-bromophenol).

[0191] preservative: Toothpaste containing calcium-based abrasives, especially chalky ones, is prone to bacterial growth. Certain preservatives, such as methyl, ethyl, butyl, propyl, and isopropyl parabens, can be particularly effective against bacterial growth. Mixtures of methyl, ethyl, butyl, and propyl parabens are especially preferred.

[0192] The activity of this mixture can be enhanced by adding phenoxyethanol. Formaldehyde and dimethylhydantoin are other preferred preservatives. Preservatives are typically included in amounts from 0.05% to 0.8% by weight.

[0193] Antioxidants: Preferred antioxidants are those that are compatible with other components and harmless to health. These include ascorbic acid, ascorbyl palmitate, thiodipropionic acid, calcium ascorbate, dilauryl dithiopropionate, guaiac, sodium ascorbate, butylated hydroxytoluene, butylated hydroxyanisole, and tocopherols. Mixtures of antioxidants may be used. When present, the antioxidants are added at a level that effectively reduces or mitigates discoloration that would otherwise result from the oxidation of the toothpaste's components. The preferred amount is 0.01% to 1% by weight.

[0194] Sweeteners: The toothpaste composition may preferably contain a sweetener. Preferred sweeteners include sodium saccharin, aspartame, triclogalactose, thaumatin, potassium butyrate, steviol glycoside, stevia extract, p-methoxycinnamate, neohesperidyl dihydrochalcone, and perilla stigma. Typical levels are from 0.005% to 5% by weight, more preferably from 0.01% to 1% by weight.

[0195] Bleach: Preferred toothpastes may include: one or more bleaching agents, such as peroxides, such as potassium peroxybisphosphate; effervescent systems, such as sodium bicarbonate / citric acid systems; color-changing systems; and 0.001 to 6% by weight, preferably 0.5% to 4% by weight, of a chelating agent, said chelating agent comprising an alkali metal salt of citric acid, an alkali metal salt of alanine, an alkali metal salt of glycine, and an alkali metal salt of serine.

[0196] The preferred choice is an alkali metal salt of citric acid, especially potassium citrate, and most preferably tripotassium citrate.

[0197] Preferred compositions may also include one or more breath strips, glitter particles, large silica particles, pellets, beads, and flavor encapsulators to enhance sensory benefits or for visual appeal.

[0198] Colorant: The compositions according to the invention may contain at least one colorant. Colorants, as used herein, include pigments, dyes, lakes, and agents that impart a particular luster or reflectivity, such as pearlescent agents. Any orally acceptable colorant may be used, including but not limited to titanium dioxide, zinc oxide, red iron oxide, yellow iron oxide, brown iron oxide, and black iron oxide, ferrous ammonium ferricyanide, manganese violet, ultramarine, titanium-treated mica, bismuth oxychloride, and mixtures thereof. One or more colorants are optionally present in a total amount ranging from 0.001% to 20% by weight, more preferably from 0.01% to 10% by weight, and still preferably from 0.1% to about 5% by weight, based on the total weight of the composition.

[0199] Titanium dioxide may also be added to the composition to obtain opacity. Titanium dioxide is typically included in an amount of 0.25 to 5% by weight.

[0200] Preferably, when measured using an aqueous solution of 1% by weight of the toothpaste composition in distilled water and measured at 25°C using a conventional pH-sensitive electrode, the pH of the toothpaste composition is 5.5 to 10.5, still preferably 6.0 to 10.0, more preferably 6.5 to 9.5, more preferably 6.5 to 9.0, and even more preferably 7.0 to 8.0.

[0201] Preferably, when the toothpaste composition is a gel toothpaste composition based on silica abrasive, the pH of the toothpaste composition is 5.5 to 7. Preferably, when the toothpaste composition is a chalk-based composition, the pH of the toothpaste composition is 8.5 to 10 when measured using an aqueous solution of 1% by weight of the toothpaste composition in distilled water and measured at 25°C using a conventional pH-sensitive electrode.

[0202] The composition according to the invention may preferably contain further ingredients commonly found in the art, such as: • Antimicrobial agents, such as chlorhexidine, sanguisorbin extract, metronidazole, quaternary ammonium compounds, such as cetylpyridium chloride; cetylpyridium chloride clay complexes, biguanides, such as chlorhexidine digluconate, hexetine, oltinidine, alexidine; and halogenated bisphenol compounds, such as 2,2'-methylenedi-(4-chloro-6-bromophenol); • Anti-inflammatory agents, such as ibuprofen, flurbiprofen, aspirin, indomethacin, etc.; • Anti-caries agents, such as sodium fluoride and stannous fluoride, amine fluoride, sodium monofluorophosphate, sodium tripolyphosphate and casein; Plaque buffers, such as urea, calcium lactate, calcium glycerophosphate, and strontium polyacrylate; • Vitamins, such as vitamin A, vitamin C, vitamin D, vitamin B (preferably B3) and vitamin E; • Plant extracts; • Plant-derived antioxidants, such as flavonoids, catechins, polyphenols, tannins, and mixtures thereof; • Desensitizing agents, such as potassium citrate, potassium chloride, potassium tartrate, potassium bicarbonate, potassium oxalate, potassium nitrate, and strontium salts; • Anti-tartar agents, such as alkali metal pyrophosphates, hypophosphite-containing polymers, organophosphonates, and citrate phosphates; • Biomolecules, such as bacteriocins, antibodies, enzymes, etc.; • Protein materials, such as collagen; ·preservative; • Sunscreen; Hyaluronic acid; • Amino acids, such as arginine; • Coloring agents; pH adjuster; Sweeteners; Flavoring agents • Pharmaceutically acceptable carriers, such as starch, sucrose, water, or water / alcohol systems; Surfactants, such as anionic surfactants, nonionic surfactants, cationic surfactants, and zwitterionic or amphoteric surfactants; • Moisturizers, such as glycerin, sorbitol, propylene glycol, xylitol, lactitol, etc.; It may also include polymer compounds that can enhance the delivery of active ingredients (e.g., antimicrobial agents); • Buffers and salts used to buffer the pH and ionic strength of the oral care composition; and • Other optional ingredients may be included, such as bleaching agents, peroxides, or potassium peroxide diphosphate. • Effervescent systems, such as the sodium bicarbonate / citric acid system, • Color variation system, etc.

[0203] According to another aspect of the invention, there is use for a packaged product for providing improved fragrance impact and / or fragrance strength, wherein the toothpaste composition comprises a bicarbonate, and wherein the toothpaste composition is encapsulated in a flexible tube comprising a multilayer laminated structure, wherein the multilayer laminated structure comprises a barrier layer comprising ethyl vinyl alcohol; and wherein the multilayer laminated structure comprises 45% to 90% by weight of at least one polyethylene having a content of 0.91 g / cm³. 3 Up to 0.99 g / cm 3 The density of the range.

[0204] According to another aspect, the present invention provides a packaged product comprising: i. A flexible laminated tube, said flexible laminated tube comprising a multilayer laminated structure; and, ii. A toothpaste composition encapsulated in a flexible tube; The toothpaste composition contains a fragrance; The multilayer laminated structure includes a) A printable layer comprising polyethylene, wherein the polyethylene comprises HDPE; b) A sealing layer comprising polyethylene, wherein the polyethylene comprises HDPE; c) Barrier layer; d) A first extruded layer for laminating the barrier layer to the printable layer; and e) A second extruded layer for laminating the barrier layer to the sealing layer; The barrier layer is a multilayer structure having a barrier material sublayer, the barrier material sublayer comprising ethyl vinyl alcohol sandwiched between a first intermediate sublayer and a second intermediate sublayer, wherein the first intermediate sublayer and / or the second intermediate sublayer comprises HDPE.

[0205] The present invention is further illustrated with reference to the following non-limiting embodiments.

[0206] Example In the lamination process, the abbreviated component identifiers have the following meanings.

[0207] Example 1 Evaluation of the flavor properties and stability of toothpaste compositions encapsulated in plastic-based laminated tubes.

[0208] Different multilayer laminated structures according to the present invention are provided in Table 1 below. The multilayer laminated structures provided below have a printable layer, a barrier layer, and a sealing layer.

[0209] A blown film having the printable layer, the barrier layer, and the sealing layer having the structures provided in Table 1 below is taken. In structure 4, the barrier layer undergoes a metallization step after the blown film process. In the metallization step, an Al coating is deposited by vapor deposition. The metallized coating has a thickness of 60 nanometers.

[0210] The barrier layer and the printable layer are laminated by extruding an LDPE film between the printable layer and the barrier layer. The sealing layer and the barrier layer are laminated by extruding an LDPE film between the barrier layer and the sealing layer.

[0211] Table 1

[0212] The flexible PBL laminated tube is prepared from the multilayer laminated structure (structures 1 to 4) described in Example 1, wherein said structure includes at least one having a density of 0.91 g / cm³. 3 Up to 0.99 g / cm 3 It is a high-density polyethylene with an ethyl vinyl alcohol barrier layer.

[0213] The toothpaste compositions based on chalk and the compositions based on silica are prepared as provided in Table 2 below.

[0214] Table 2

[0215] The formulations provided in Table 2 were then packaged in two different laminated tubes made of a multilayer laminated structure 1 (given in Table 1 above), and the tubes were stored at 45°C for 3 months. The flavor impact and properties, as well as the product stability, were studied at regular intervals of 1 month, and the data were recorded and provided in Table 3 below.

[0216] Table 3

[0217] The data provided in Table 3 show that when toothpaste compositions are packaged in flexible tubes comprising a multilayer laminated structure with an EVOH barrier layer according to the invention, fragrance impact and properties are maintained even under adverse storage conditions. The laminated structure according to the invention exhibits good fragrance impact and properties, as well as storage stability, in different toothpaste compositions having silica-based abrasives (Example 1) and chalk-based abrasives (Example 2).

[0218] Example 3 Evaluation of the flavor and stability of toothpaste compositions encapsulated in PBL tubes according to the invention when compared to commercially available packaged products in PBL and ABL tubes.

[0219] The toothpaste composition described in Example 2 was tested in three different tubes under different temperature and humidity conditions, as shown below. The samples were stored at different temperature points for 3 months, after which the tubes were washed and the loss of fragrance (extractable from lamination) in the toothpaste was determined (in percentage of increased fragrance).

[0220] Table 4

[0221] As can be seen from Table 4 above, the toothpaste composition exhibits better stability and lower fragrance adsorption onto the laminated tube when stored in the PBL laminated tube prepared according to the present invention.

Claims

1. Packaged products, including: i. A flexible laminated tube, the flexible laminated tube comprising a multi-layer laminated structure; and, ii. A toothpaste composition encapsulated in a flexible tube; The toothpaste composition said therein contains fragrance; and, The multilayer laminated structure includes a barrier layer. The barrier layer is a multilayer structure having a barrier material sublayer, the barrier material sublayer comprising ethyl vinyl alcohol sandwiched between a first intermediate sublayer and a second intermediate sublayer, wherein the first intermediate sublayer and / or the second intermediate sublayer comprises high-density polyethylene (HDPE). The multilayer laminated structure comprises 45% to 90% by weight of at least one polyethylene, wherein the at least one polyethylene has a content of 0.91 g / cm³. 3 Up to 0.99 g / cm 3 The density of the range; and The multilayer laminated structure includes at least one extruded laminate layer.

2. The packaged product according to claim 1, wherein the at least one polyethylene is selected from high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and combinations thereof.

3. The packaged product according to claim 1, wherein the multilayer laminate structure includes a printable layer comprising polyethylene, wherein the polyethylene comprises HDPE.

4. The packaged product according to any one of claims 1 to 3, wherein the multilayer laminate structure includes a sealing layer comprising polyethylene, wherein the polyethylene comprises HDPE.

5. The packaged product of claim 4, wherein the sealing layer comprises additional polyethylene selected from MDPE, LDPE or LLDPE, more preferably, the sealing layer comprises HDPE and MDPE in combination with or in combination with LLDPE or LDPE.

6. The packaged product according to any one of claims 1 to 5, wherein the barrier layer has a structure of at least 5 layers, the 5-layer structure comprising a first intermediate sublayer, a first connecting sublayer, a barrier material sublayer containing EVOH, a second connecting sublayer, and a second intermediate sublayer.

7. The packaged product according to any one of claims 1 to 6, wherein the first intermediate sublayer and / or the second intermediate sublayer comprising HDPE comprises 75% or more HDPE by weight of the sublayer, more preferably 100% HDPE by weight of the sublayer.

8. The packaged product according to any one of the preceding claims, wherein the multilayer laminate has a thickness ranging from 50 micrometers to 300 micrometers, preferably from 60 micrometers to 250 micrometers.

9. The packaged product according to any one of the preceding claims, wherein the ethylene-vinyl alcohol copolymer has 20 mol% to less than 38 mol% ethylene, preferably 25 mol% to less than 38 mol% ethylene, more preferably 25 mol% to less than 35 mol% ethylene, and preferably 29 mol% to less than 35 mol% ethylene.

10. The packaged product according to any one of the preceding claims, wherein the barrier material sublayer comprising an ethylene vinyl alcohol copolymer has a thickness ranging from 5 micrometers to 15 micrometers, more preferably 6 micrometers to 15 micrometers, 10 micrometers to 13 micrometers, more preferably 10 micrometers to 11 micrometers.

11. The packaged product according to any one of the preceding claims, wherein the barrier layer comprises a metal layer, preferably wherein the metal layer has a thickness of no more than 100 nanometers.

12. The packaged product according to any one of the preceding claims, wherein the total HDPE content in the multilayer laminate structure is no more than 70% by weight, more preferably no more than 49% by weight, and still preferably no more than 37% by weight, based on the total weight of the multilayer laminate structure.

13. The packaged product according to any one of the preceding claims, wherein the polyethylene comprises recycled polyethylene, more preferably post-consumer recycled polyethylene, and even more preferably the recycled polyethylene is HDPE.

14. The packaged product according to any one of the preceding claims, wherein the toothpaste composition comprises 0.1 to 5% by weight, preferably 0.1 to 1.5% by weight, of fragrance.

15. Packaged products, including: i. A flexible laminated tube comprising a multi-layered laminated structure; and, ii. A toothpaste composition encapsulated in a flexible tube; The toothpaste composition contains a fragrance; The multilayer laminated structure includes: a) A printable layer comprising polyethylene, wherein the polyethylene comprises HDPE; b) A sealing layer comprising polyethylene, wherein the polyethylene comprises HDPE; c) Barrier layer; d) A first extruded layer for laminating the barrier layer to the printable layer; and e) A second extruded layer for laminating the barrier layer to the sealing layer; The barrier layer is a multilayer structure having a barrier material sublayer, the barrier material sublayer comprising ethyl vinyl alcohol sandwiched between a first intermediate sublayer and a second intermediate sublayer, wherein the first intermediate sublayer and / or the second intermediate sublayer comprises HDPE.

Citation Information

Patent Citations

  • Recycled and recyclable barrier laminate tube

    US20230405982A1